2018
DOI: 10.1021/acs.chemrestox.8b00193
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Bases of Lead-Induced Toxicity in Mammalian Systems and Possible Mitigations

Abstract: The effects of lead exposure on mammals are reported to be devastating. Lead is present in all the abiotic environmental components such as brass, dust, plumbing fixtures, soil, water, and lead mixed imported products. Its continuous use for several industrial and domestic purposes has caused a rise in its levels, thereby posing serious threats to human health. The mechanisms involved in lead-induced toxicity primarily include free-radical-mediated generation of oxidative stress which directly imbalances the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 52 publications
2
47
0
2
Order By: Relevance
“…Several plant extracts [ 49–51 ] are known to have antioxidant properties against oxidative stress in different organs and xenobiotics. [ 52–56 ] The results showed that lipid peroxidation and MDA level in the spinal cord tissue increased in Cup group and EA 100 mg/kg co‐treatment with Cup reversed this undesirable alteration compare with Cup group. Increased ROS production, oxidative phosphorylation dysfunction, and calcium hemostasis imbalance and decreased antioxidant defense system in serum and cerebrospinal fluid were reported in MS disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several plant extracts [ 49–51 ] are known to have antioxidant properties against oxidative stress in different organs and xenobiotics. [ 52–56 ] The results showed that lipid peroxidation and MDA level in the spinal cord tissue increased in Cup group and EA 100 mg/kg co‐treatment with Cup reversed this undesirable alteration compare with Cup group. Increased ROS production, oxidative phosphorylation dysfunction, and calcium hemostasis imbalance and decreased antioxidant defense system in serum and cerebrospinal fluid were reported in MS disease.…”
Section: Discussionmentioning
confidence: 99%
“…There was no effect of the solvent on human DNA. Lane [15]. The results of the present in vitro study indicated that the extracts of leaves of T. peruviana and A. mexicana were causing damage to DNA isolated from different living systems whereas C. limon was able to protect the DNA from damage in the concentration dependent manner.…”
Section: Effect Of T Peruviana On Insect Dna and Protection By C Limentioning
confidence: 61%
“…Calcium homeostasis is crucial for cell survival, [91] and lead binds to calcium-activated proteins with higher affinity than calcium itself. The neurotoxic effects of lead are connected to this ability to substitute calcium in biological functions and interfere with ion channels and pumps, [92] which is also the how lead passes through the blood brain barrier. [93] Lead affects the CNS and gives lower IQ, behavioral changes and learning deficits.…”
Section: Lead Halide Perovskitesmentioning
confidence: 99%